Screening of Herbal Fractions for Antibiotic Drug Resistance Reversal - Singh, Gurdeep (My University, 2007)
The increasing phenomenon of acquisition of resistance among microorganisms towards antimicrobial drugs is attributed due to their indiscriminate and improper use of current antimicrobial and the genetic plasticity of microorganisms converting them into drug resistant super infectious agents. These are difficult to treat and are responsible for variety of chronic infections. The problem of microbial resistance is growing and the outlook for the use of antimicrobial drugs in the future is still uncertain. Therefore, actions must be taken to control the use of antibiotic, develop research to better understand the genetic mechanisms of resistance, and to continue studies to develop new drugs, either synthetic or natural. Natural products produced from plant extracts have great potential as antimicrobial compounds against drug resistant microorganisms. Staphylococcus aureus is a commensal organism cited as major hospital acquired pathogen and strains of this species are becoming resistant to practically all classes of antibiotics. Most of the Methicillin-Resistant Staphylococcus aureus (MRSA) strains are rapidly becoming resistant to Ciprofloxacin (Fluoroquinolone). As the antimicrobial drug resistance in microorganisms increases rapidly, there is a continual need for a pipeline of new agents or NON-OTC (Over the counter) drug formulations to combat antimicrobial drug resistance in microorganisms. Plants produce scores of phytochemicals, which have the innate ability to be used as antimicrobial drugs. However, there are some phytochemicals, which enhance the bioactivity of other compounds, referred to as biopotentiators or bioenhancers. These bioenhancers also work as synergists by reverting the antimicrobial drug resistance. The mechanisms of drug resistance reversal are being looked at for development of newer and effective drugs formulations of bioenhancers with resistant drug to overcome antimicrobial drug resistance.
Keywords: Herbal Fractions; Mic; Staphylococcus Aureus; Mrsa; Mueller-Hinton Agar